Cyanobacterial Transposons Tn5469 and Tn5541 Represent a Novel Noncomposite Transposon Family - Schaefer, Michael R. (American Society for Microbiology, 1998)
A noncomposite transposon, designated Tn5541, was isolated from strain Fd33 of the filamentous cyanobacterium Fremyella diplosiphon UTEX 481. Sequence analysis showed that Tn5541 is structurally and genetically very similar to Tn5469, which is also endogenous to F. diplosiphon. Both Tn5469 and Tn5541 encode homologous forms of an unusual composite transposase and a protein of unknown function. DNA hybridization analysis showed that like Tn5469, Tn5541 was not widely distributed among cyanobacterial genera. A similar analysis showed that Tn5469 and Tn5541 were equally limited to and present as multiple genomic copies in three of six distinct strains comprising the Tolypothrix 1 cluster of heterocyst-forming filamentous cyanobacteria. These and other distinguishing features suggest that Tn5469 and Tn5541 represent a novel noncomposite transposon family.